Optimized RNA ISH, RNA FISH and protein-RNA double labeling (IF/FISH) in Drosophila ovaries. - Zimmerman, S.G.; Peters, N.C.; Altaras, A.E.; Berg, C.A. (Nature Protocols, 2013)
In situ hybridization (ISH) is a powerful technique for detecting nucleic acids in cells and tissues. Here we describe three ISH procedures that are optimized for Drosophila ovaries: whole-mount, digoxigenin-labeled RNA ISH; RNA fluorescent ISH (FISH); and protein immunofluorescence (IF)-RNA FISH double labeling (IF/FISH). Each procedure balances conflicting requirements for permeabilization, fixation and preservation of antigenicity to detect RNA and protein expression with high resolution and sensitivity. The ISH protocol uses alkaline phosphatase-conjugated digoxigenin antibodies followed by a color reaction, whereas FISH detection involves tyramide signal amplification (TSA). To simultaneously preserve antigens for protein detection and enable RNA probe penetration for IF/FISH, we perform IF before FISH and use xylenes and detergents to permeabilize the tissue rather than proteinase K, which can damage the antigens. ISH and FISH take 3 d to perform, whereas IF/FISH takes 5 d. Probe generation takes 1 or 2 d to perform.